Apparent life threatening events (ALTE): diagnostic approach - Erick Manuel Toro-Monjaraz; Eduardo Cázares-Ramírez (Instituto Nacional de Pediatría, 2014)
Apparent Life-Threatening Events (ALTE) are a form of clinical presen- tation of various problems or diseases in children under one year of age. A frequency of 0.6/1000 newborns is estimated. In Mexico, there is no known incidence, systematic approach or guidelines for hospital discharge, so we performed a literature review. Its etiology may be gastrointestinal, neurological, cardiovascular, metabolic, endocrine or-idiopathic. The detailed history and physical examination provide an outline to select the laboratory and imaging studies to perform.